Implementasi Syariah Compliance pada Akad Murabahah dan Ijarah (Studi Kasus Pada KSPPS BMT Fastabiq Jepara) - Silvia Dora Bonita; Aan Zainul Anwar (JESI (Jurnal Ekonomi Syariah Indonesia), 2017)
This study aims to determine: 1) the principles of financing agreement murabaha and Ijarah in accordance with Islamic law, 2) the implementation of the financing agreement murabaha and Ijarah, and 3) the factors that caused the broken promise in murabaha and ijarah financing agreement in BMT Fastabiq Jepara well as a way to resolve. This research is a field research with a qualitative approach, the research has the characteristics that the data declared in a state appropriately or as their (natural setting), with no change in the shape of symbols or numbers and descriptive based on questions how. And data processing technique is to use a qualitative descriptive technique. The results of the analysis show that: 1) The principles of murabaha financing agreement on BMT Fastabiq Jepara accordance with Islamic sharia as the murabaha financing agreement executed included also wakalah. The principle of Ijarah financing agreement yet on BMT Fastabiq Jepara accordance with Islamic sharia because it is not included wakalah in it. 2) Execution of Murabahah and Ijarah financing agreement in Jepara Fastabiq BMT carried out according to established procedures BMT Fastabiq Jepara. And 3) the factors that led to broken promises in murabaha and Ijarah financing agreement in BMT Fastabiq Jepara is internal and external factors. The steps undertaken BMT Fastabiq Jepara in overcoming these factors include identifying the problem, if there is a problem that complicated it will be a step family, but if they can not be resolved then it will be taken legal action.